DAMPAK PENERAPAN PRINSIP NATIONAL TREATMENT TERHADAP IKLIM INVESTASI DI INDONESIA PASCA UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Abdul Halim Barkatullah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Investment is the driving force of a country's economy. The state's obligation to regulate investment is due to the complexity of the nature of investment and has an impact on many aspects, ranging from land, labor, capital, taxation and other aspects. The principle of